Special education in Brazilian educational policies: A historical approach - Luana Leal Ribeiro; Renata Maldonado da Silva (Arizona State University, 2019)
Historically, the schooling of people with disabilities was offered in a precarious and segregated way from the students considered as "normal". As a result of the advancement of concepts, regulations and new perspectives on special education students, the educational practices offered to such individuals were reformulated in the last decades of the 20th century. The present work seeks to present some of the main world milestones in different historical times on how the issue of disability and disabled people were treated, showing the evolution in the treatment given, in relation to the achievements and effects of rights directed to them. Together with the main historical milestones, this work focus on the first signs of the schooling of the person with disabilities and the paths taken by them before the conception of an inclusive perspective in regular schools. In order to reach this objective, references were used to discuss the subject, and an extensive document analysis of the norms present in the Brazilian educational legislation was conducted. Despite the advances and norms that contemplate the guidelines of the concept of inclusive education, it is worth emphasizing that it is still necessary to question the effectiveness of the existing actions planned for special education, and if they are in agreement with the established precepts about what actually contemplates an education that is in fact inclusive.